1969
DOI: 10.1143/jjap.8.588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crystallographic Orientation on Mobility, Surface State Density, and Noise in p-Type Inversion Layers on Oxidized Silicon Surfaces

Abstract: Experimental results are reported concerning the anisotropy of surface state density, N s s , 1/f-type equivalent noise voltaze, V N , and field effect mobilitv, µ F E , in p-channel MOS transistors with various crystallographic orientations in <011> and <001> zones. The amounts of V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 13 publications
3
46
0
Order By: Relevance
“…Mobility on a (110) unstrained surface is found roughly 2.5 times higher than on a standard (001) wafer, in agreement with earlier measurements [36]. It was found that biaxial tensile stress decreases mobility on a (001) surface [15,16].…”
Section: Modeling Of P-channel Mosfetssupporting
confidence: 90%
“…Mobility on a (110) unstrained surface is found roughly 2.5 times higher than on a standard (001) wafer, in agreement with earlier measurements [36]. It was found that biaxial tensile stress decreases mobility on a (001) surface [15,16].…”
Section: Modeling Of P-channel Mosfetssupporting
confidence: 90%
“…3 However, the device performance and the uniformity can be improved further by control of the crystallographic orientation of the channel of the TFTs. It is well known that electronic properties of metal oxide semiconductor field effect transistors 4,5 ͑MOSFETs͒ have a pronounced dependence on the surface and in-plane crystal orientations with respect to the direction of the current flow due to the anisotropy of the effective mass. If the surface and even the in-plane orientations in the channel of the TFTs can be controlled in the location controlled grain, this grain will be ideal for c-Si TFT fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…This is typically accomplished by keeping transistors in northsouth orientation on the wafer, but by using a wafer with the crystal orientation rotated by 45 deg. The orientation of the surface normal (from channel to dielectric to electrode) also has an impact upon carrier mobility 50,51 . There is preferential surface orientation for both electrons and holes and it is not the same.…”
Section: Channel and Gate Engineeringmentioning
confidence: 99%